Incorporation of dried water hyacinth, Eichhornia crassipes in red tilapia, Oreochromis mossambicus x O. niloticus fingerlings feeds - Abdel-Rahman Tibin, Mubarak Eisa (Terengganu: Universiti Malaysia Terengganu, 2014)
Traditionally, fish meal has been utilized extensively in aqua-feeds, mainly due to its high nutritional properties. However, various reasons dictate the utilization of sustainable alternatives and minimizing the dependence on this commodity in fish feeds. Lack of affordable fish feeds is one of the major constraints facing small- scale fish farmers as most of the fish feed is imported by majority of the countries practicing aquaculture. Hence, the aim of the present study was to evaluate the nutritional potential of the water hyacinth(WH), Eichhornia crassipes dried meal and also to investigate effects on nutrients digestibility growth performance and feed utilization of dried WH meal incorporated in feeds fed to fingerling hybrid red tilapia, Oreochromis mossambicus x O. niloticus.